Research of Laser Beam Combining in Ring Fiber-Optic Delay Line - M. R. Zaripov; V. A. Alekseev; A. I. Kirillov; A. V. Oficerova (Приборы и методы измерений)
At present time widespread use of autonomous laser systems supposes reducing of supply energy, consumed by laser sources that are included in their composition and at the same time increasing of their output energy characteristics. The objective of this work was practical confirmation of possibility of laser beam combining in systems based on a ring delay line.The experimental setup that implements the principle of synchronous laser beam combining scheme on the ring fiber-optic delay line, developed by authors earlier, is made. The schematic diagram of the manufactured setup is presented, its operation principle is described in detail and its composition is considered. It is noted that in order to achieve the objective measurements of electrical signals received from the photodetector of the setup and measurements of the part of laser radiation power removed by the splitter and formed in the fiber-optic path of the setup are performed. Results of measurements are presented as the waveforms of electrical signals from the photodetector and of power values at the output of the splitter. Plots of dependence of the output power and the circulation power on the power of the initial laser beam introduced into the setup are presented.Analysis of results showed that the laser beam combining occurs in the ring fiber-optic delay line. Besides, it was found that the proposed scheme provides an increase in the power of the initial beam by 1.05…1.11 times.